PENGARUH DEBIT AIR PENDINGIN DAN POSISI KONDENSOR TERHADAP HASIL KONDENSASI PIROLISIS GETAH PINUS - Syah, Fahma Ilmian (Sainteknol : Jurnal Sains dan Teknologi, 2020)
The experiment aim to know the effect of cooling water flow rate and condenser position to the pyrolysis product and the heat transfer rate occurring on the condenser. Flow rate of water as condenser coolantabout 2 L / min, 3 L / min 4 L / min, and 5 L / min. Position of condenser used is horizontal, vertical and slopeabout 45 degree. These variables are used to evaluate the performance of the condenser through the acquisitionof condensed oil and heat transfer rate. The result of the research shows that flow rate of condenser coolantgreatly influences the amount of pine sap oil produced. Increase of condenser coolant water flow the volumeof pine sap oil produced is increasing. The condenser position also affects the amount of volume of pine sapoil produced. The larger the angle of the condenser slope the volume of pine sap oil produced decreases. Thehighest amount of oil is produced at flow rate 5 L / min at a horizontal condenser position with an oil amountof 71 ml, and the least amount of oil produced at a flow rate 2 L / min in a vertical position with an oil amountof 54 ml. The Result show that number of heat transfer increase along with increasing flow rate of condensercoolant. Its due baecause cooling water flow rate more absorp of heat. The greater the angle of the slope at thecondenser the heat transfer rate is greater. Increasing angle of slope causes the fluid flow rate to be slower dueto head loss.